2014
DOI: 10.4236/ojog.2014.41009
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a hand-held lactate meter in measuring umbilical cord blood lactate at all lactate levels

Abstract: Objective: Fetal scalp lactate has largely replaced pH analysis to assess intrapartum hypoxia. Many obstetrics units use hand-held lactate meters to measure umbilical blood because of its affordability and ease of use. We sought to investigate the agreement of Lactate Pro TM with a reference method blood gas analyser and to determine its usefulness with a recommended cutoff value of 4.8 mmol/L. Methods: Prospective study carried out at a tertiary institution where 237 arterial and 233 venous samples from umbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…in fi eld conditions. Moreover the portable analyzers could be more practical to use during some critical interventions [11,12]. The latest studies showed the introduction of the lactate pocket analyzer in ovine medicine [13].…”
mentioning
confidence: 99%
“…in fi eld conditions. Moreover the portable analyzers could be more practical to use during some critical interventions [11,12]. The latest studies showed the introduction of the lactate pocket analyzer in ovine medicine [13].…”
mentioning
confidence: 99%